Structure of Lō‘ihi Seamount, Hawai‘i and Lava Flow Morphology From High-Resolution Mapping - Clague, David A.; Paduan, Jennifer B.; Caress, David W.; Moyer, Craig L.; Glazer, Brian T.; Yoerger, Dana R. (Frontiers in Earth Science, 2019)
High-resolution bathymetric data were collected using AUV Sentry at the summit and at two hydrothermal vent fields on the deep south rift of L¯o‘ihi Seamount. The summit map records a nested series of caldera and pit crater collapse events, uplift of one resurgent block, and eruptions that formed at least five low lava shields that shaped the summit. The earliest and largest caldera, formed ~5900 years ago, bounds almost the entire summit plateau. The resurgent block was uplifted slightly more than 100 m and has a tilted surface with a dip of about 6.5° towards the SE. The resurgent block was then modified by collapse of a pit crater centered in the block that formed West Pit. The shallowest point on L¯o‘ihi’s summit is 986 m deep and is located on the northwest edge of the resurgent block. Several collapse events culminated in formation of East Pit, and the final collapse formed Pele’s Pit in 1996. The nine mapped collapse and resurgent structures indicate the presence of a shallow crustal magma chamber, ranging from depths of ~1 km to perhaps 2.5 km below the summit, and demonstrate that shallow sub-caldera magma reservoirs exist during the late pre-shield stage. On the deep south rift zone are young medium- to high-flux lava flows that likely erupted in 1996 and drained the shallow crustal magma chamber to trigger the collapse that formed Pele’s Pit. These low hummocky and channelized flows had molten cores and now host the FeMO hydrothermal field. The Shinkai Deep hydrothermal site is located among steep-sided hummocky flows that formed during low-flux eruptions. The Shinkai Ridge is most likely a coherent landslide block that originated on the east flank of L¯o‘ihi.